Trabalho docente em salas multisseriadas na escola ribeirinha Dondon Pinheiro localizada no rio Paruru – Abaetetuba/PA - PINHEIRO, Erica Pinheiro (2022)
Despite the advances achieved in recent years, the education of the field still faces several problems, among which the multiseriated classes can be highlighted. Thus, by knowing this reality closely, the main objective of this research is: to know how the teaching work is performed in multiseriated classes in the context of a riverside school, in order to point out the main difficulties faced by the teacher for the realization of quality teaching. To this end, a semi-structured interview was conducted with a teacher, systematic observation in the classroom and visits to documents made available by the school, in which it was possible to verify that there are several difficulties imposed on teaching work, both structural and school buildings in poor conditions, lack of recreational area, library and other minimally necessary spaces, as pedagogical difficulties with lack of continuing education, students of different age groups and levels of knowledge living in the same space, work overload, teacher illness and professional devaluation. Thus, it is imperative that changes happen, in which it is necessary a more appropriate look of the public power and greater organization of the school community.